LEARNING PROCESS IN ANALYTIC GEOMETRY COURSE USING IGNATIAN PEDAGOGICAL PARADIGM - Agustin, Sara Sarita; Santoso, Eko Budi (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2025)
This study examines the implementation of the Ignatian Pedagogical Paradigm (IPP) in Analytic Geometry instruction and assesses student outcomes following its application. Given the importance of holistic education in mathematics instruction, this study explores how IPP can enhance both cognitive and affective student development. A qualitative approach was employed, with the data collected through evaluation sheets measuring competence, compassion, conscience, and commitment among 14 undergraduate students at Universitas Sanata Dharma. The IPP was implemented through its five stages: context, experience, reflection, action, and evaluation. The findings suggest that IPP fosters deeper conceptual engagement, ethical development, and teamwork through attitudes that promote holistic learning. However, challenges were encountered in assessing the depth of student reflections, particularly in evaluating students’ ability to critically analyze their learning experiences and in measuring the consistency of individual commitment within group activities. This study contributes to educational research and practice by providing a comprehensive overview of the application of IPP in Analytic Geometry learning and demonstrating its potential to foster meaningful, holistic education while identifying areas for improvement in assessment practices.